Nano phosphors for light emitting diodes (LEDs) Syntheses and Characterization - Murthy, K.V.R (Recent Research in Science and Technology, 2012)
Syntheses of phosphors for Light Emitting Diodes (LEDs) of various host matrices by different preparative methods are very import and need of the day for the phosphor industry. Role of preparative variables in synthesis of nano phosphors and display phosphors along with basic requirements are discussed in the present paper. Nano phosphors are preferred over micron size phosphors in a number of applications not only due to their particle size but also better optical properties. Some of the techniques such as solid state diffusion, flame and laser pyrolysis and sol-gel process are being employed to manufacture. The main advantages nanophosphors in potential applications such as solid state lighting, medical, security, displays, remote thermometry and thermoluminescence radiation dosimetry. The present paper discusses the synthesis of display phosphors applicable in Color Picture Tube (CPT) and Plasma Display Panels (PDP) and Phosphor coated LEDs (PLED) for lighting applications.